The use of Facebook to build a community for distance learning students: a case study from the Open University. (1st September 2016) - Callaghan, George; Fribbance, Ian
Abstract: Social media platforms such as Facebook are commonplace throughout society. However, within higher education institutions such networking environments are still in the developmental stage. This paper describes and discusses case study data from the Open University's Faculty of Social Science Facebook page. It starts by giving an overview of the literature surrounding social media in higher education before examining how the Social Sciences Faculty at the Open University has used Facebook to help build an academic community. Data includes numerical information on number of likes, demographic data on students who use the page, analysis on the type and nature of comments and more qualitative extracts from postings related to academic questions. It also discusses challenges and difficulties with using such social media tools in a university environment and suggests fruitful areas for future research.